Successful Management of Massive Air Embolism During Cardiopulmonary Bypass Using Multimodal Neuroprotection Strategies (2019)
Complications and critical events during cardiopulmonary bypass (CPB) are very challenging, difficult to manage, and in some instances have the potential to lead to fatal outcomes. Massive cerebral air embolism is undoubtedly a feared complication during CPB. If not diagnosed and managed early, its effects are devastating and even fatal. It is a catastrophic complication and its early diagnosis and intraoperative management are still controversial. This is why the decision-making process during a massive cerebral air embolism represents a challenge for the entire surgical, anesthetic, and perfusion team. All caregivers involved in this event must synchronize their responses quickly, harmoniously, and in such a way that all interventions lead to minimizing the impact of this complication. Its occurrence leaves important lessons to the surgical team that faces it. The best management strategy for a complication of this type is prevention. Nevertheless, a surgical team may ultimately be confronted with such an occurrence at some point despite all the prevention strategies, as was the case with our patient. That is why, in each institution, no effort should be spared to establish cost-effective strategies for early detection and a clear and concise management protocol to guide actions once this complication is detected. It is the duty of each surgical team to determine and clearly organize which strategies will be followed. The purpose of this case study was to demonstrate that a massive air embolism can be rapidly detected using near-infrared spectroscopy monitoring and can be successfully corrected with a multimodal neuroprotection strategy. © The Author(s) 2018.